Integrating Information Flow Analysis in Unifying Theories of Programming - Mu, Chunyan; Li, Guoqiang (Proceedings (IEEE Pacific Rim International Symposium on Dependable Computing), 2021)
This paper presents a formal approach for modelling and reasoning about information flow control in software systems under Hoare and He's Unifying Theories of Programming (UTP). We investigate the problem of integrating information flow control into system design in a unified semantic setting. Our approach can therefore treat information flow analysis and control in various families of specification languages and programming paradigms in a more general way. In addition, we formalise the link between classes of predicates as a paired function which maps set of the predicates from one class into set of the predicates from the other with a concern of flow security preservation. The proposed flow-sensitive combined theories of multiple level classes of predicates can be applied to ensure flow security in different paradigms under stepwise development.